Evaluation of the congenital supravalvular aortic stenosis by different imaging modalities. Issue 9 (6th July 2017) - Guner, Ahmet; Havan, Nuri; Gunduz, Sabahattin; Akgun, Taylan; Guvendi, Busra; Kahveci, Gokhan
Abstract : A 36‐year‐old female was admitted to hospital exhibiting chest pain, dyspnea, and a heart murmur on the right upper sternal border, radiating to both carotid arteries. The blood pressure of the patient's right arm exceeded the pressure in the left by 25 mm Hg (Coanda effect). In spite of laboratory results that did not fall outside the expected range, the left ventricle was revealed to be hypertrophic following electrocardiography. Transthoracic echocardiography revealed a severe supravalvular aortic stenosis (SVAS) with a peak Doppler velocity of 6.04 cm/s and an estimated mean pressure gradient of 89 mm Hg, with moderate aortic and mitral regurgitation. Contrast‐enhanced computed tomography (CCT) indicated a partial hourglass‐shaped narrowing of the ascending aorta. Lesions associated with supravalvular stenosis of the pulmonary artery, patent ductus arteriosus, and aortic coarctation were ruled out by the CCT. Congenital SVAS is a rare heart condition, and three anatomically distinct forms have been described. The most common type is the "hourglass, " which produces a marked thickening and disorganization of the aortic tissue, producing a constricting annular ridge at the superior margin of the sinuses of Valsalva.